Negative interference with antibody-dependent cellular cytotoxicity mediated by rituximab from its interactions with human serum proteins - Yanaka, Saeko; Yogo, Rina; Yagi, Hirokazu; Onitsuka, Masayoshi; Wakaizumi, Natsumi; Yamaguchi, Yuki; Uchiyama, Susumu; Kato, Koichi (Frontiers in Immunology, 2023)
Although interactions of small molecular drugs with serum proteins have been widely studied from pharmacokinetic and pharmacodynamic perspectives, there have been few reports on the effects of serum components on therapeutic antibody functions. This study reports the effect of abundant serum proteins on antibody-dependent cellular cytotoxicity (ADCC) mediated by rituximab and Fcγ receptor III (FcγRIII). Human serum albumin (HSA) and the Fab fragment from the pooled serum polyclonal IgG were found to compromise ADCC as non-competitive inhibitors. Our nuclear magnetic resonance data provided direct evidence for the interactions of HSA with both the Fab and Fc regions of rituximab and also with the extracellular region of FcγRIII (sFcγRIII). The degree of involvement in the interaction decreased in the order of rituximab-Fab > rituximab-Fc > sFcγRIII, suggesting preferential binding of HSA to net positively charged proteins. Although much less pronounced than the effect of HSA, polyclonal IgG-Fab specifically interacted with rituximab-Fc. The NMR data also showed that the serum protein interactions cover the Fc surface extensively, suggesting that they can act as pan-inhibitors against various Fc receptor-mediated functions and pharmacokinetics. Our findings highlight the importance of considering serum–protein interactions in the design and application of antibody-based drugs with increased efficacy and safety.